Gastric bypass: the Slovenian experience – preliminary results - Breznikar Brane; Dinevski Dejan; Skalicky, Marjan (Acta Medico-Biotechnica, 2021)
We evaluated the short–term outcomes for laparoscopic Roux–en–Y gastric bypass surgery in 100 patients with a follow–up of 2–39 months. Consecutive patients who met the criteria for bariatric surgery set by the International Federation for the Surgery of Obesity were offered laparoendoscopic Roux–en–Y gastric bypass between February 2007 and March 2010. A 30–mL pouch, 60–cm biliopancreatic limb, and 100–150–cm Roux limb was created using a linear stapler using five trocar incisions. No patients died. The prevalence of conversion to open gastric bypass was 2%. Excess weight loss (EWL) at 12 months and 24 months was 69.6% and 76.5%, respectively. Resolution or improvement of type–II diabetes mellitus and hypertension was 93.7% and 97.0%, respectively. The Bariatric Analysis and Reporting Outcome System (BAROS) quality–of–life (QoL) score in the groups with and without comorbidities was evaluated to be “very good”: 6.5 and 3.2, respectively. Four early major complications (leakage, ileus, stenosis of end–to–end anastomosis, iatrogenic lesion of the small intestine) were observed. A late complication of internal hernia occurred in one patient. Gastric bypass is effective and safe in achieving weight loss and improving comorbidities and QoL.